Elephants - Hurt, Avery; National Geographic Society (U.S.) (Washington, D.C. : National Geographic, 2016)
Stomp around the African savanna, run around the forests of India, take a mud bath, and more as you learn all about elephants! Discusses the physical characteristics, behavior, habitats, and life cycle of elephants.
OSLIS\Gale Nat Geo eBooks(2/2/23).
Includes index.
Ages 2-5.
Description based on print version record.
Keywords: Elephants -- Juvenile literature; Elephants; Elephants; JUVENILE NONFICTION -- Reader -- Beginner; Elephants; Electronic books- OSLIS; Juvenile works; Electronic books